The role of GLP-1 in the postprandial effects of acarbose in type 2 diabetes. Issue 3 (March 2021) - Dalsgaard, Niels B; Gasbjerg, Lærke S; Hansen, Laura S; Hansen, Nina L; Stensen, Signe; Hartmann, Bolette; Rehfeld, Jens F; Holst, Jens J; Vilsbøll, Tina; Knop, Filip K
Abstract : Aims: The alpha-glucosidase inhibitor acarbose is believed to reduce plasma glucose by delaying hydrolysis of carbohydrates. Acarbose-induced transfer of carbohydrates to the distal parts of the intestine increases circulating glucagon-like peptide 1 (GLP-1). Using the GLP-1 receptor antagonist exendin(9–39)NH2, we investigated the effect of acarbose-induced GLP-1 secretion on postprandial glucose metabolism in patients with type 2 diabetes. Methods: In a double-blinded, placebo-controlled, randomized, crossover study, 15 participants with metformin-treated type 2 diabetes (age: 57–85 years, HbA1c: 40–74 mmol/mol) were subjected to two 14-day treatment periods with acarbose or placebo, respectively, separated by a 6-week wash-out period. At the end of each period, two randomized 4-h liquid mixed meal tests with concomitant infusion of exendin(9–39)NH2 and saline, respectively, were performed. Results: Compared to placebo, acarbose increased postprandial GLP-1 concentrations and decreased postprandial glucose. We observed no absolute difference in the exendin(9–39)NH2 -induced increase in postprandial glucose excursions between placebo and acarbose periods, but relatively, postprandial glucose was increased by 119 ± 116% (mean ± s.d. ) during exendin(9–39)NH2 infusion in the acarbose period vs a 39 ± 27% increase during the placebo period ( P  = 0.0163). Conclusions: We confirm that acarbose treatment stimulates postprandial GLP-1 secretion in patients with type 2 diabetes. Using exendin(9–39)NH2, we did not see an impact of acarbose-induced GLP-1 secretion on absolute measures of postprandial glucose tolerance, but relatively, the effect of exendin(9–39)NH2 was most pronounced during acarbose treatment.